Analysis and Prediction of Learning Effect Based on Data Mining Algorithm and Sports System - Yan, Shi (2022 Second International Conference on Advanced Technologies in Intelligent Control, Environment, Computing & Communication Engineering (ICATIECE), 2022)
The progress. However, for school teaching, there is still no operable software, especially in school physical education teaching, which is facing the realistic problem of huge workload. Therefore, this paper analyzes the effect Learning Based. This study aims to explore the relationship between physical education learning and students' performance. In this study, data mining technology is used to analyze students' physical education achievements. The researcher used descriptive statistics, correlation coefficient analysis, regression analysis and factor analysis physical education learning and student performance. In researcher also analyzed the influence of gender, age group, school type (public or private), subject field (mathematics or Science) and other variables on physical education learning according to the grade level.